2015
DOI: 10.1515/ijamh-2014-0036
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of fat-free mass to resting energy expenditure: implications for weight loss strategies in the treatment of adolescent obesity

Abstract: Owing to the strong relationship between fat-free mass (FFM) and resting energy expenditure (REE), the preservation of FFM is often emphasized in the treatment of adolescent obesity. Typical treatment regimens including an increased dietary consumption of protein and participation in resistance training are common components of adolescent weight management programs, despite limited evidence of a positive influence of FFM on weight loss outcomes in adolescents. Given the larger volume of FFM in obese relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
(77 reference statements)
1
10
0
Order By: Relevance
“…FM had not changed during all periods, and FFM showed similar changes as REE. This result supported that FFM is the largest contributor to REE. We have shown that FFM was not significantly different between preconception and a few weeks after delivery, whereas Berggren et al .…”
Section: Discussionsupporting
confidence: 85%
“…FM had not changed during all periods, and FFM showed similar changes as REE. This result supported that FFM is the largest contributor to REE. We have shown that FFM was not significantly different between preconception and a few weeks after delivery, whereas Berggren et al .…”
Section: Discussionsupporting
confidence: 85%
“…These factors are mainly determined by body size, food intake, physical activity and body composition. Body fat has a five‐fold lower contribution to resting energy expenditure compared to that of fat‐free mass, ~3.5 kcal kg −1 day −1 versus ~18 kcal kg −1 day −1 respectively (Browning & Evans, ; Wang et al., ). In the present study, kittens with a higher BCS also had a higher body fat percentage.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle itself comprises about 40% of total body weight and thus contributes substantially to energy expenditure as it is a prominent constituent of RMR [ 9 ]. Furthermore, considering that RMR comprises ~65% of TEE, skeletal muscle mass plays an essential role in determining TEE [ 9 , 10 ]. Paradoxically, while AA seem to have a greater percentage of relative skeletal muscle mass, they exhibit lower RMR making them more susceptible to overnutrition [ 7 , 11 ].…”
Section: Mitochondrial Efficiency Increases Predisposition Of African...mentioning
confidence: 99%